2006
DOI: 10.1002/app.22921
|View full text |Cite
|
Sign up to set email alerts
|

Phase interactions and structure evolution of heterophasic ethylene–propylene copolymers as a function of system composition

Abstract: Heterophasic copolymers comprised of polypropylene (PP) matrix and ethylene-propylene copolymer (EPC) dispersed phase were investigated with respect to the dispersed phase composition, i.e., ethylene/propylene ratio. The rheological properties, morphology, as well as thermal and mechanical relaxation behavior were studied to describe the structure evolution and phase interactions between the components of the PP copolymers. Decrease of the ethylene content of the EPC leads to a higher matrix-dispersed phase co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
49
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 41 publications
7
49
0
Order By: Relevance
“…Scanning Electron Microscopy (SEM) investigations of the polymers showed that the melt viscosity of the dispersed EPR phase, represented by the intrinsic viscosity of XCS fraction, significantly affects the size and distribution of EPR particles. This is in line with theory and was reported by a number of research groups (compare [17][18][19][20][21][22] and [25][26][27][28]). Unlike in previous studies, the particles' cross sections were not considered to be circular but taken to be elliptically shaped as a result of the orientation in the processing step.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Scanning Electron Microscopy (SEM) investigations of the polymers showed that the melt viscosity of the dispersed EPR phase, represented by the intrinsic viscosity of XCS fraction, significantly affects the size and distribution of EPR particles. This is in line with theory and was reported by a number of research groups (compare [17][18][19][20][21][22] and [25][26][27][28]). Unlike in previous studies, the particles' cross sections were not considered to be circular but taken to be elliptically shaped as a result of the orientation in the processing step.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the particles are smaller in the high shear skin region than in the core of the specimens. Although this is in line with literature (compare [17][18][19][20][21][22] and [25][26][27][28]), the determined diameters are not reflecting the actual shape of EPR the particles. The particles are oriented and elongated during the filling of the mold.…”
Section: Results and Discussion 31 Morphologysupporting
confidence: 85%
See 1 more Smart Citation
“…A look at the corresponding DSC results in Table 3 however shows the absence of crystalline PE even at higher C2(XCS), quite in contrast to results normally found for ZNC-based EP-HECOs. Doshev et al [3] reports clear melting points for the PE phase of ZNC-grades from 70 wt% C2(XS) upwards, i.e. very close to the composition of PP/EP68.…”
Section: Results and Discussion 31 Composition And Morphologymentioning
confidence: 82%
“…In general it should be noted that while numerous reports deal with the effect of viscosity ratio of PP/EPR blend systems as well as their ternary counterparts, PP/EPR/PE blends, on morphology [4,15,16,[25][26][27], the effect of EPR composition on the same has been studied significantly less [2,3,5,[28][29][30]. In both cases a decisive parameter of polymer blend theory is modified, and both for the viscosity ratio as for the compatibility the change can be effected for the matrix component as well as for the disperse one.…”
Section: Results and Discussion 31 Composition And Morphologymentioning
confidence: 99%